Microdosing flexibility in an efficient supply chain. Issue 3 (5th October 2020) - Saunders, Lance W.; Merrick, Jason R.W.; Holcomb, Mary C.
Abstract: The designation of a supply chain as efficient or responsive has often been considered to be a dichotomy in theory and practice. This technical note explores this issue by describing an engagement by the research team with a large consumer packaged‐goods company within their cosmetics supply chain during the launch of a new product family. The company was experiencing high supply–demand mismatch costs that they attributed to their supply chain that was designed to emphasize efficiency over responsiveness. We analyzed the appropriateness of the supply‐chain design through the lens of theory and concluded that the efficient design was in fact a good match for the product. A simulation model allowed us to organize available data and identify the root cause of the mismatch costs. Results from the simulation showed that the mismatch costs stemmed primarily from a failure to deploy small but important responsiveness opportunities: Because the supply chain was designated as efficient, responsiveness was ignored, and this substantially increased mismatches. Mismatches also occurred because decision makers failed to distinguish between delivery and decision lead time.